ANALISIS PENGGUNAAN WATER COOLED CONDENSER PADA MESIN PENGKONDISIAN UDARA PAKET (AC WINDOW) - Wirawan, IKG; Putra Wibawa, Ngurah (Jurnal Energi Dan Manufaktur; Vol 2, No.2 Desember 2007)
One of the important aspects in thermal design is refrigeration and air conditioning. Working principle of air conditioning is absorption and thermal dissipation process. Condenser is main component to release the heat from refrigerant to the cooling medium. In the present research, water cooled condenser was used to replace the commonly air condenser. Pressure and temperature at some section of the components were observed in order to examine the performance of the air conditioning system. The results showed that the COP varied from 9.66 to 12.4; refrigerationg effect varied from 1.31 kW to 1.86 kW; cooling capacity varied from 0.38 TR to 0.53 TR; and heat transfer varied from 2.2 kW to 2.98 kW.
Keywords: Refrigeration, water cooled condenser, cooling effect, cooling capacity